Transformasi Pengetahuan Sains Tradisional menjadi Sains Ilmiah dalam Proses Produksi Jamu Tradisional - Sudarmin Sudarmin; Rayandra Asyhar (Universitas Jambi, 2012)
Transformation of the traditional sciences into a scientific knowledge of traditional jamu production by local community of Cilacap, Center Java, has been studied. The research was intended to transfrom the original science of Jawa community into scientific knowledge. The output of the research is a set of scientific kenowledge as a result of reconstruction of the original sciences of Jawa community, i.e. in processing traditional Jamu, and it can be used by science teachers as a learning source or a contextual model of teaching in a classroom activities. This research is a descriptive-qualitative research, and the researchers were involved directly in collecting data, i.e. observation, interview, discussion, and collection of informations and documents. The data were analysed, verified, transformed into scientific knowledge, and interpreted to obtain the meaningful information. Focus of the research is a tradition of Cilacap community in producing traditional Jamu, including the production process, types of jamu and its effect to human health. The research concludes that traditional science producing traditional jamu can be transformed into a set of scientific knowledge.